Characterization and optimization of fluorescein isothiocyanate labeling of humanized h2E2 anti-cocaine mAb - Terence L. Kirley; Andrew B. Norman (Biochemistry and Biophysics Reports, 2023)
Fluorescein isothiocyanate (FITC) is widely used to fluorescently label reactive lysine residues on proteins, including antibodies. The rate and extent of labeling varies with reaction conditions, concentration of label, and the concentration and nature of the protein. Fluorescently labeled proteins are very useful, and one use for FITC labeled mAbs is development of assays to measure anti-mAb antibodies produced in vivo during treatment with antibody therapeutics. Our laboratory has developed a humanized anti-cocaine mAb (h2E2) intended for the treatment of cocaine use disorders. Thus, a well characterized FITC labeled h2E2 mAb is needed to quantitate possible anti-mAb antibodies. The time course of labeling and the relative incorporation of FITC into the heavy and light chains, as well as into the Fab and Fc portions of the mAb, was assessed. A novel use of differential scanning fluorimetry in the absence of any extrinsic fluorophore was developed and demonstrated to be capable of measuring antigen (cocaine) binding. In addition, the effect of increasing degrees of labeling by FITC on the thermodynamic parameters driving the binding of cocaine to the mAb was assessed via isothermal titration calorimetry (ITC). This binding technique, unlike others developed recently to measure cocaine binding, is not dependent on, or subject to interference by, the absorbance or fluorescence of the incorporated FITC label. The methods and results reported herein guide the optimization of FITC labeling needed for anti-mAb assays and other assays important for the development of therapeutic mAbs, which are some of the most specific and clinically useful drugs available.